“Cada um aprende de um jeito”: das adaptações às flexibilizações curriculares - Scherer, Renata Porcher (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation discusses and analyzes the meanings of curriculum adaptations that have been produced and triggered by legal documents and pedagogical journals. In order to perform this analysis, the research has been positioned in the articulation of two fields: Curriculum Studies and Foucauldian Studies, which have contributed to the view of curriculum as a cultural artifact that shapes our way of being in the world, and to the problematization of the present by suspecting of the neoliberal logic that has supported our contemporary ways of thinking and acting. The concept of discourse has been used as a theoretical and methodological tool to address, organize and analyze the volume of information produced from the examination of two sets of materials – (1) legal documents: Warnock Report (1979), Adaptaciones Curriculares (1992), Adaptaciones Curriculares. Guía para su elaboración (1993), Special Education Policy (1994), Salamanca Statement (1994), Necesidades educativas especiales y aprendizaje escolar (1995), National Education Guidelines (1996), National Curriculum Parameters: Curriculum Adaptations (1998), National Special Education Guidelines in Basic Education (2001), Operational Guidelines for Specialized Educational Assistance (2009), Inclusive School and strategies to face it: curriculum adaptations (2010); (2) pedagogical journals: 13 issues of Nova Escola journal (one from 2003, one from 2004, one from 2005, three from 2006, two from 2009, one from 2010, two from 2012, and two from 2013); four issues of Pátio journal (one from 2005, one from 2009, one from 2010, and one from 2012). The research results have enabled us to state that: (1) curriculum adaptations were constituted from several national and international movements prior to the publication of Brazilian legal documents regulating school inclusion; (2) in the analyzed period, from 1979 to 2012, there was a change in emphasis from curriculum adaptations to curriculum flexibilization. Such displacement is related to the change from a disciplinary society, with an emphasis on the constitution of docile subjects, to a control society, with a focus on the constitution of flexible subjects. By intensifying control mechanisms, flexibility has been strengthened, thus allowing us to state that we now live under the flexibility imperative; (3) the psychological discourses have been reinforced in the articulation with neuroscience discourses. The latter have turned towards Education and invested in the constitution of psychologized students who will have their interests, paces and individual characteristics respected at school, favoring both the emergence of curriculum adaptations and the displacement from adaptations to flexibilization; (4) flexibility has become stronger in the constitution of flexible teachers, and it behooves the teacher to design strategies to teach all the students, respecting that each student has a particular way to learn.
Keywords: Adaptações curriculares; Flexibilizações curriculares; Currículo; Inclusão escolar; Discurso; Curriculum adaptations; Curriculum flexibilization; Curriculum; School inclusion; Discourse; ACCNPQ::Ciências Humanas::Educação